Bending of a symmetric piezothermoelastic laminated plate with a through crack - Shindo, Y.; Domon, W.; Narita, F. (Archives of Mechanics, 1997)
Following the theory of linear piezoelectricity, we consider the response of a cracked composite plate with attached piezoelectric polyvinylidene fluoride layers subjected to mechanical, thermal and electric field loading. Piezoelectric layers are added to the upper and lower surfaces. Classical lamination theory is extended to include piezothermoelastic effects, and the bending problem of a symmetric piezoelectric laminated plate with a through crack is considered. Fourier transforms are used to reduce the problem to the solution of a pair of dual integral equations. The integral equations are solved exactly and the moment intensity factor is expressed in closed form.